A case report of Krukenbergs tumor with cutaneous seeding - Banavasi Shanmukha Girisha; Tonita Mariola Noronha; Akshata C Alva; Preethi B Nayak (Indian Journal of Medical and Paediatric Oncology)
A 47-year-old female patient presented with painless skin colored and erythematous papules coalesced to form plaques over lower abdomen for 10 days. She had undergone exploratory laparotomy with hysterectomy and bilateral oophorectomy 1 month ago, and histopathology was reported as Krukenbergs tumor. She was getting evaluated for primary, when she was referred to dermatology. A clinical diagnosis of cutaneous infiltration of tumor was made, and biopsy was done from a representative lesion which showed features suggestive of metastatic poorly differentiated adenocarcinoma. In the majority of cases in the past, cutaneous metastasis is seen much later in the course of the disease. High degree of suspicion and histopathology was helpful in the diagnosis of underlying malignancy in our patient.